LEARNING STRATEGIES TOWARDS READING SKILLS DEVELOPMENT - Ridha Aska Amanda; Fazri Nur Yusuf (Soegijapranata Catholic University, 2008)
Identified as the core skill in academic setting. the importance of reading skill is deniable. This study investigated reading strategies employed by 8th graders of a public school in Bandung. It aimed at identifying the most frequent-used reading strategies and discovering their similarities and differences between higher and lower achievers. This study employed questionnaires and interviews to collect data. The findings of this study suggested that cognitive strategies are the most frequently-used strategies. Both higher and lower achievers were identified using nine high-frequency strategies. The differences were in identifying appropriateness and willingness to use the strategies. and students' intreat in reading materials. As a conclusion. higher and lower achievers might have different reading strategies due to time allotment. reading frequency, and strategic investment. Therefore. highlighting reading strategies is vital. and having a more comprehensive. integrated class room based reading study is strongly required.